2016
DOI: 10.14348/molcells.2016.0233
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Changes in Neurodegenerative Diseases

Abstract: Afflicted neurons in various neurodegenerative diseases generally display diverse and complex pathological features before catastrophic occurrence of massive neuronal loss at the late stages of the diseases. This complex nature of neuronal pathophysiology inevitably implicates systemwide changes in basic cellular activities such as transcriptional controls and signal cascades, and so on, as a cause. Recently, as one of these systemwide cellular changes associated with neurodegenerative diseases, epigenetic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 84 publications
0
17
0
Order By: Relevance
“…Similar to polyQ diseases, AD and PD also manifest epigenetic alterations, though the mechanisms of which remain to be elucidated [20, 31]. Nevertheless, treatment with certain epigenetic drugs, such as HDAC inhibitors, ameliorated AD and PD phenotypes in animal models [31], indicative of the relevance and importance of epigenetic alterations in the disease pathogenesis.…”
Section: Protein Toxicity In the Nucleusmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to polyQ diseases, AD and PD also manifest epigenetic alterations, though the mechanisms of which remain to be elucidated [20, 31]. Nevertheless, treatment with certain epigenetic drugs, such as HDAC inhibitors, ameliorated AD and PD phenotypes in animal models [31], indicative of the relevance and importance of epigenetic alterations in the disease pathogenesis.…”
Section: Protein Toxicity In the Nucleusmentioning
confidence: 99%
“…This view proposes that the more soluble protofibrillar or oligomeric aggregates (as opposed to the more mature fibrillar aggregates formed inside the nucleus) have toxic properties in afflicted neurons [ 14 18 ]. Whether or not the nuclear inclusion bodies are the major source of nuclear protein toxicity, nuclear dysfunctions such as transcriptional alteration and impaired nucleocytoplasmic transport are evident in many cases of neurodegenerative diseases [ 19 , 20 ].…”
Section: Protein Toxicity In the Nucleusmentioning
confidence: 99%
“…Besides, in AD brains histone modifications have been linked to the reduction in transcription of genes that are implicated in neuronal physiology and increased the transcription of genes that are normally silenced (Berson et al, 2018). The phosphorylated histone H3 presents an altered localization of the cytoplasm, while the levels of the acetylated histone H4 are decreased in AD patients (Kwon et al, 2016).…”
Section: Dna Damage and Repairmentioning
confidence: 99%
“…This reaction is catalyzed by DNA methyltransferases using S-adenosylmethionine as the source of the methyl group.There is increasing evidence that epigenetic mechanisms of gene expression are involved in the development of neurodegenerative diseases. 3,4 In recent years, ascorbic acid has been found to have a role in epigenetic mechanisms of gene expression. 5 In 2013, several groups showed that ascorbic acid serves as a cofactor for the ten-eleventen translocation (TET) dioxygenases.…”
mentioning
confidence: 99%
“…5 Abnormalities in the concentrations and/or activities of 5mC and 5hmC in the brain have been implicated in the development of neurodegenerative diseases. 4,10 As ascorbic acid is associated with 5mC and 5hmC, abnormalities in the concentration and/or activity of ascorbic acid in the brain could be associated with the development of these diseases. I suggest that in addition to the ways by which ascorbic acid may be associated with neurodegenerative diseases suggested by Moretti et al, 1 ascorbic acid could also be associated epigenetically with the development of neurodegenerative diseases.…”
mentioning
confidence: 99%